Membangun Karakter Bangsa Melalui Penguatan Identitas Nasional : Tantangan di Era Global: Tantangan di Era Global - Adzaki, Muhammad Fikri (Maliki Interdisciplinary Journal, 2025)
National identity is the identity of a nation that is the basis for maintaining the integrity and stability of the country. In the era of increasingly rapid globalization and digitalization, the flow of foreign information and culture flows freely throughout the world, including Indonesia. This has positive impacts such as easy access to information and knowledge, but also presents serious challenges to the preservation of national values. Society, especially the younger generation, is increasingly exposed to a consumptive, individualistic, and hedonistic lifestyle that shifts the values ​​of politeness, mutual cooperation, and love for local culture. This article discusses the urgency of strengthening national identity through integrative character education and the active involvement of all elements of the nation. Schools, families, and communities have an important role in instilling the values ​​of Pancasila, love of the homeland, and nationalism. In addition, social media needs to be utilized positively as a means of promoting culture and spreading national values. Thus, strengthening national identity can be a fortress in facing global challenges while forming a generation of a strong and characterful nation.